2021
DOI: 10.3390/ijerph18168480
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Determinants in Alcohol, Tobacco and Cannabis Consumption, Mood and Bullying during Adolescence

Abstract: The present study aimed to explore the differences in the consumption of alcohol, tobacco and cannabis, mood and bullying between adolescents. A cross-sectional study was carried out in five regions of Northern Spain (one in Galiza and four in central Catalonia) that share similar socioeconomic characteristics and encompass around 10,000 inhabitants each. Students living in Burela, Galiza (N = 71) were compared to those of Central Catalonia (N = 193). The independent variable was the municipality of residence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, this study replicated earlier Spanish and international findings where a greater availability of money by the adolescent is positively related to greater consumption (Burdzovic Andreas et al, 2016; Rial et al, 2018). A recent study has simultaneously evaluated family affluence and pocket money in Spain, which showed results similar to those reported in this study (Díaz‐Geada et al, 2021). Nevertheless, continuing studying this finding would be interesting to assess whether it is replicated with other samples, in longitudinal studies, or through a deep analysis of the relationship of cannabis use with other explicative variables.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study replicated earlier Spanish and international findings where a greater availability of money by the adolescent is positively related to greater consumption (Burdzovic Andreas et al, 2016; Rial et al, 2018). A recent study has simultaneously evaluated family affluence and pocket money in Spain, which showed results similar to those reported in this study (Díaz‐Geada et al, 2021). Nevertheless, continuing studying this finding would be interesting to assess whether it is replicated with other samples, in longitudinal studies, or through a deep analysis of the relationship of cannabis use with other explicative variables.…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana is recognized as one of the most controversial and socially accepted illegal drugs, becoming the most consumed drug during the last decade (Díaz-Geada et al, 2021; United Nations Office on Drugs and Crime [UNODC], 2021a). In Europe, prevalence is five times higher than other illicit drugs (Díaz-Geada et al, 2021;UNODC, 2021a). In Africa, annual prevalence was 6.4% and in Asia there are 61.5 million users (UNODC, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…During adolescence, the social influences of the peer group or friends, together with other variables such as family and school, can have an impact on the consumption of harmful substances [ 4 ]. During adolescence, the onset of alcohol consumption is more rapid, mainly due to peer group or social group membership [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the research topic of psychosocial aspects and substance use has been studied and addressed in the scientific literature [ 4 , 6 , 9 ], the present research develops an explanatory model according to the gender of the participants. Through this model, it is possible to study the existing relationships between the variables that make up each model, providing greater precision in the study of the effect of some variables on others.…”
Section: Introductionmentioning
confidence: 99%